Usefulness of spectral domain optical coherence tomography in assessing the clinical course of idiopathic intracranial hypertension: A case series - Vrinda Viswanath; R Neena (Kerala Journal of Ophthalmology)
To assess the clinical corelation of optical coherence tomography and the clinical course of idiopathic intracranial hypertension with a case series of 4 patients diagnosed with IIH and presented to a tertiary eye care centre over a 1 year period (2020-2021). Ethics committee approval taken on 12th Oct 2020. A detailed history and complete ophthalmic examination including best corrected visual acuity (BCVA), color vision, pupils, dilated fundus examination, visual fields, and OCT were done on all visits. OCT PP RNFL thickness was found to correlate with an increase and decrease in disk edema; however, in the presence of optic atrophy, mGCL was found to be a better predictor of ongoing axonal damage. A valid relationship was found between the patient’s clinical course, visual field changes as well as the RNFL and GCL parameters in OCT. Serial OCTs have a useful role in predicting the course and prognosis of the disease and can aid in altering treatment modalities.